2022
DOI: 10.3390/cimb44090276
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nanoparticles and Melatonin for Cryopreservation of Gametes and Embryos

Abstract: Cryopreservation of gametes and embryos, a technique widely applied in human infertility clinics and to preserve desirable genetic traits of livestock, has been developed over 30 years as a component of the artificial insemination process. A number of researchers have conducted studies to reduce cell toxicity during cryopreservation using adjuvants leading to higher gamete and embryo survival rates. Melatonin and Nanoparticles are novel cryoprotectants and recent studies have investigated their properties such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 160 publications
0
3
0
Order By: Relevance
“…Among the tested antioxidant agents, the most efficient in mitigating the cryodamage in human spermatozoa was melatonin, as reported in a recent meta-analysis [144]. Indeed, the addition of the hormone, a physiological regulator of the circadian rhythm, to cryoprotectants exerts a significant positive effect on sperm progressive motility and viability [144], is currently used for the cryopreservation of spermatozoa from several animal species [149][150][151] and has been also shown to improve the survivability of oocytes and embryos [148]. Such beneficial effects are not surprising considering that melatonin, besides showing antioxidant activity, is an anti-apoptotic and ROS scavenging agent [147].…”
Section: Possible Strategies To Prevent the Damage And New Approaches...mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the tested antioxidant agents, the most efficient in mitigating the cryodamage in human spermatozoa was melatonin, as reported in a recent meta-analysis [144]. Indeed, the addition of the hormone, a physiological regulator of the circadian rhythm, to cryoprotectants exerts a significant positive effect on sperm progressive motility and viability [144], is currently used for the cryopreservation of spermatozoa from several animal species [149][150][151] and has been also shown to improve the survivability of oocytes and embryos [148]. Such beneficial effects are not surprising considering that melatonin, besides showing antioxidant activity, is an anti-apoptotic and ROS scavenging agent [147].…”
Section: Possible Strategies To Prevent the Damage And New Approaches...mentioning
confidence: 99%
“…Kumar et al [125] have shown that mitoquinone, a mitochondrial-targeted antioxidant, both attenuates ultrastructural changes and protects several proteins involved in sperm key functions from alterations induced by vitrification. Emerging studies in the last few years have investigated the effects of the supplementation of freezing media with taurine and hypotaurine [145,146], melatonin [147,148] and gallic acid [25] as antioxidants. Some beneficial effects have been reported with taurine and its precursor hypotaurine which slightly but significantly improved sperm parameters, including DNA integrity, when supplemented to extenders both for standard cryopreservation [146] and vitrification [145] methods.…”
Section: Possible Strategies To Prevent the Damage And New Approaches...mentioning
confidence: 99%
“…In addition, CP causes mitochondrial dysfunction, which was the first finding in our study, providing an idea to reduce or treat the sequelae caused by chemotherapy. MT has been shown to protect frozen gamete embryos, leading to higher gamete and embryo survival rates [39]. This would suggest that MT could be used as a potential drug to treat chemotherapy-induced fertility dysfunction, which might allow women with impaired reproductive function due to chemotherapy to have better embryos or even regain fertility.…”
Section: Discussionmentioning
confidence: 99%